2007
DOI: 10.1111/j.1740-1461.2007.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Defendants Pay What Juries Award? Post‐Verdict Haircuts in Texas Medical Malpractice Cases, 1988–2003

Abstract: Legal scholars, legislators, policy advocates, and the news media frequently use jury verdicts to draw conclusions about the performance of the tort system. However, actual payouts can differ greatly from verdicts. We report evidence on post‐verdict payouts from the most comprehensive longitudinal study of matched jury verdicts and payouts. Using data on all insured medical malpractice claims in Texas from 1988–2003 in which the plaintiff received at least $25,000 (in 1988 dollars) following a jury trial, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Several studies report some of the largest malpractice awards that made headlines ultimately resulted in settlements that were only between 5% and 10% of the original jury verdict [18,39,41,42]. Using closed-claim files from Texas, Hyman et al found that 75% of plaintiffs received a payout less than the verdict [18].…”
Section: Postverdict Adjustments: More About the Jury Trial In Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies report some of the largest malpractice awards that made headlines ultimately resulted in settlements that were only between 5% and 10% of the original jury verdict [18,39,41,42]. Using closed-claim files from Texas, Hyman et al found that 75% of plaintiffs received a payout less than the verdict [18].…”
Section: Postverdict Adjustments: More About the Jury Trial In Contextmentioning
confidence: 99%
“…Using closed-claim files from Texas, Hyman et al found that 75% of plaintiffs received a payout less than the verdict [18]. The average settlement for all cases was 29% less than the verdict; and the larger the verdict amount, the greater was the reduction during posttrial proceedings.…”
Section: Postverdict Adjustments: More About the Jury Trial In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hyman et al (2007) use data on 7 Note that these studies acknowledge that the causality may be reversed-instead of reforms improving insurer profitability, insurer behavior may determine a states' willingness to enact reforms. The mechanisms through which tort reforms influence premiums are important to understand so that empirical models can account for the complexities.…”
Section: A the Theoretical Relationship Between Caps And Premiumsmentioning
confidence: 99%
“…Setting aside purely strategic appeals, some degree of settlement activity results from the normal forces at work in litigation at the posttrial stage (Hyman et al 2007). Moreover, on some level, appeals settlement …”
Section: Appeal Dropoutsmentioning
confidence: 99%